Concretes with binary mixtures of artificial pozzolans and concrete demolition waste - Lima, Cristian Jonathan Franco de; Ribeiro, Francisco Roger Carneiro; Isaia, Geraldo Cechella; Mancio, Mauricio (Ambiente Construído, 2020)
The objective of this study is to analyse the use of binary mixtures of pozzolanic materials and concrete demolition waste in concrete mixtures, especially the resulting mechanical properties and durability. A total of ten concrete formulations were produced distinguishing them in different types using different Portland cements, different artificial pozzolans and coarse aggregates from concrete demolition. The particular properties of each formulation were verified by testing the axial compressive strength, longitudinal modulus of elasticity and penetration of chloride under immersion. Substitutions were of 15% w.t. and 30% w.t. natural coarse aggregate substituted with concrete demolition waste and, in the case of binary mixtures, additional 25% w.t. of the binder agglomerate substituted with rice husk ash or fly ash. Results showed that the final strength to axial compression and modulus of elasticity of concrete mixtures were negatively affected by utilising demolition waste, but this effect was balanced by adding supplementary cementitious materials. Regarding the durability test, it was found that the lowest coefficients occurred in the mixtures using CP V-ARI, together with artificial pozzolans, in mixtures with 15% w.t. substitution of natural aggregate with recycled aggregate. It was concluded that using recycled aggregates in concrete is viable but conditioned to the concomitant use of pozzolanic materials.